2012
DOI: 10.5194/bg-9-1225-2012
|View full text |Cite
|
Sign up to set email alerts
|

Organohalogen emissions from saline environments – spatial extrapolation using remote sensing as most promising tool

Abstract: Abstract. Due to their negative water budget most recent semi-/arid regions are characterized by vast evaporates (salt lakes and salty soils). We recently identified those hypersaline environments as additional sources for a multitude of volatile halogenated organohalogens (VOX). These compounds can affect the ozone layer of the stratosphere and play a key role in the production of aerosols. A remote sensing based analysis was performed in the Southern Aral Sea basin, providing information of major soil types … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…Although most of these organohalogens have been discovered in the marine environment, various chemical and biological processes producing organohalogens have been identified in the terrestrial environment as well. The presence of volatile and non-volatile trihalomethyl compounds (especially trichloromethane, trichloroacetic acid, trichloroacetyl-containing compounds -the model compounds of this review) in unpolluted terrestrial environments has been shown in for example temperate forests, grasslands and peatlands (Hoekstra et al, 1999;Haselmann et al, 2000a;Dimmer et al, 2001;McCulloch, 2003;Peters, 2003;Albers et al, 2010a), boreal forests (Hellén et al, 2006), wet tundra (Rhew et al, 2008b), subtropical shrub lands and hypersaline arid soil (Kotte et al, 2012), salt marshes (Rhew et al, 2008a) and rice paddies (Khalil et al, 1990). The frequent detection of trichloromethyl compounds in soils and groundwater in absence of other anthropogenic contaminants suggests strongly that these halogenated compounds are produced naturally by biogeochemical processes (Laturnus et al, 2000;Albers et al, 2010a;Hunkeler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these organohalogens have been discovered in the marine environment, various chemical and biological processes producing organohalogens have been identified in the terrestrial environment as well. The presence of volatile and non-volatile trihalomethyl compounds (especially trichloromethane, trichloroacetic acid, trichloroacetyl-containing compounds -the model compounds of this review) in unpolluted terrestrial environments has been shown in for example temperate forests, grasslands and peatlands (Hoekstra et al, 1999;Haselmann et al, 2000a;Dimmer et al, 2001;McCulloch, 2003;Peters, 2003;Albers et al, 2010a), boreal forests (Hellén et al, 2006), wet tundra (Rhew et al, 2008b), subtropical shrub lands and hypersaline arid soil (Kotte et al, 2012), salt marshes (Rhew et al, 2008a) and rice paddies (Khalil et al, 1990). The frequent detection of trichloromethyl compounds in soils and groundwater in absence of other anthropogenic contaminants suggests strongly that these halogenated compounds are produced naturally by biogeochemical processes (Laturnus et al, 2000;Albers et al, 2010a;Hunkeler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the higher organic matter content in soils. Based on a 24-h production time under moist conditions and elevated summer temperatures leading to topsoil temperatures of up to 55 8C, [29] a soil density of 1.3 g cm À3 and 1-cm soil depth, our data are extrapolated to high MeCl production rates of 650 mmol m À2 day À1 . For comparison, Rhew et al [6] found similarly large MeCl fluxes from salt marshes of up to 570 mmol m À2 day À1 , but production was related to plant activity.…”
Section: Resultsmentioning
confidence: 99%
“…A rewetting and drying-out cycle is typical for SW Australian salt lakes. Kotte et al [29] reported high emissions of MeCl and MeBr from dry samples of similar environments in south Russia and Namibia. But areas of regressing (salt) lakes such as the Aral Sea could also contribute to thermolytic emissions.…”
Section: Assessment Of Thermolytic Dms and Mecl Formation In Hypersalmentioning
confidence: 98%
“…A few years later, the organohalogen emissions from salt lakes and salt-affected soils were investigated on a broader scale by combining microcosm experiments and remote sensing. [28] For an area of 15 000 km 2 in the southern Aral Sea basin, fluxes of 16 873 g day À1 in the cover area for C 2 H 2 Cl 2 (dichloroethene) were estimated. Recently, it was shown that pH-neutral to alkaline hypersaline lake sediments from Western Australia also contribute to the global emissions of halogenated hydrocarbons and that biotic processes dominate the emissions.…”
mentioning
confidence: 99%